Safer destinations, healthier staff and happier tourists: Opportunities for inclusive water, sanitation and hygiene in tourism. (October 2021) - Loehr, J.; Dwipayanti, N.M.U.; Nastiti, A.; Powell, B.; Hadwen, W.; Johnson, H.
Abstract: Sustainable tourism development, including tourism's COVID-19 recovery, requires a holistic view of environmental and community benefits, including access to water, sanitation and hygiene (WASH). This study presents a system-wide Inclusive WASH in tourism framework for destinations. Using a qualitative approach including interviews and focus groups, the framework is applied at three system scales: hotels, the community and wider destination to assess the current WASH situation in Mandalika, Lombok, Indonesia, a water-scarce destination earmarked for rapid development. Findings highlight differences in Inclusive WASH practices between hotels and communities, the potential for conflict and gendered inequalities. Barriers linked to system elements, structure and the enabling environment are identified. Addressing inequitable planning processes, improving stakeholder engagement and creating tools for hotels to improve Inclusive WASH can contribute to improving destination value. Findings are relevant for practitioners, government and community organisations integrating Sustainable Development Gaols 5 and 6 into tourism development and recovery. Highlights: Significant differences exist between WASH practices of hotels and communities. Hotels can deliver over the fence WASH benefits to host-communities. Barriers are linked to system elements, system structure and enabling environment. Cooperation between stakeholders is critical to destination-wide WASH outcomes. Integrated approach to Inclusive WASH will contribute to tourism recovery.